Do big athletes have big hearts? Impact of extreme anthropometry upon cardiac hypertrophy in professional male athletes. (24th October 2012) - Riding, Nathan R; Salah, Othman; Sharma, Sanjay; Carré, François; O'Hanlon, Rory; George, Keith P; Hamilton, Bruce; Chalabi, Hakim; Whyte, Gregory P; Wilson, Mathew G
Abstract : Aim: Differentiating physiological cardiac hypertrophy from pathology is challenging when the athlete presents with extreme anthropometry. While upper normal limits exist for maximal left ventricular (LV) wall thickness (14 mm) and LV internal diameter in diastole (LVIDd, 65 mm), it is unknown if these limits are applicable to athletes with a body surface area (BSA) >2.3 m 2 . Purpose: To investigate cardiac structure in professional male athletes with a BSA>2.3 m 2, and to assess the validity of established upper normal limits for physiological cardiac hypertrophy. Methods: 836 asymptomatic athletes without a family history of sudden death underwent ECG and echocardiographic screening. Athletes were grouped according to BSA (Group 1, BSA>2.3 m 2, n=100; Group 2, 2–2.29 m 2, n=244; Group 3, <1.99 m 2, n=492). Results: There was strong linear relationship between BSA and LV dimensions; yet no athlete with a normal ECG presented a maximal wall thickness and LVIDd greater than 13 and 65 mm, respectively. In Group 3 athletes, Black African ethnicity was associated with larger cardiac dimensions than either Caucasian or West Asian ethnicity. Three athletes were diagnosed with a cardiomyopathy (0.4% prevalence); with two athletes presenting a maximal wall thickness >13 mm, but in combination with an abnormal ECG suspicious of an inherited cardiac disease. Conclusion: Regardless of extreme anthropometry, established upper limits for physiological cardiac hypertrophy of 14 mm for maximal wall thickness and 65 mm for LVIDd are clinically appropriate for all athletes. However, the abnormal ECG is key to diagnosis and guides follow-up, particularly when cardiac dimensions are within accepted limits.